Therapeutic potential of PPARα agonist in ligature-induced experimental periodontitis (Journal of Applied Oral Science, 2022)
Inflammation-related immune responses and bone metabolism lead to extensive tooth loss in periodontitis. Objective: This study aims to investigate the effect of peroxisome proliferator-activated receptor (PPAR) alpha agonist anti-inflammatory treatment in vitro and in ligature-induced experimental periodontitis in vivo . Methodology: Splenocytes were isolated from C57BL/6J mice and cultured for 48 hours under the following conditions: control, P. gingivalis lipopolysaccharide (LPS) (1 µg/ml); experimental, LPS (1 µg/ml) + PPARα agonist (fenofibrate) at 1, 10, 50, 100 µM. MRNA and secreted protein levels of TNF-α expression were detected by RT-qPCR and ELISA, respectively. Silk ligatures (7-0) were tied around maxillary second molars of C57BL/6J mice for two weeks. Optimized doses of fenofibrate (50 µM) and vehicle control were injected into the contralateral side of the palatal gingiva on days three, six, and nine. At day 14, bone resorption, osteoclastogenesis, and gingival mRNA expression levels of TNF-α, IL-1β, IL-6, and RANKL/OPG were measured by micro-computed tomography, Tartrate-resistant acid phosphatase (TRAP) staining, and Real-time quantitative PCR, respectively. Results: TNF-α expression in cultured spleen cells were significantly increased in the presence of LPS, when compared with the control group, and significantly reduced by fenofibrate treatment in a dose-dependent manner from 1-100 µM (p<0.05). Gingival mRNA levels of TNF-α, IL-1β, IL-6, and the ratio of RANKL/OPG, were significantly decreased after injection of fenofibrate, when compared to the control side (p<0.05). Periodontal bone loss and TRAP positive cell formation were significantly decreased on the side with an injection of fenofibrate, as compared to the control side (p<0.05). Conclusions: An anti-inflammatory treatment, PPARα agonist, inhibited inflammation and periodontal bone loss in ligature-induced experimental periodontitis.